Fatty acid-induced β cell apoptosis: A link between obesity and diabetes - Shimabukuro, Michio (The National Academy of Sciences, 1998)
Like obese humans, Zucker diabetic fatty (ZDF) rats exhibit early β cell compensation for insulin resistance (4-fold β cell hyperplasia) followed by decompensation (>50% loss of β cells). In prediabetic and diabetic ZDF islets, apoptosis measured by DNA laddering is increased 3- and >7-fold, respectively, compared with lean ZDF controls. Ceramide, a fatty acid-containing messenger in cytokine-induced apoptosis, was significantly increased (P < 0.01) in prediabetic and diabetic islets. Free fatty acids (FFAs) in plasma are high (>1 mM) in prediabetic and diabetic ZDF rats; therefore, we cultured prediabetic islets in 1 mM FFA. DNA laddering rose to 19.6% vs. 4.6% in lean control islets, preceded by an 82% increase in ceramide. C(2)-Ceramide without FFA induced DNA laddering, but fumonisin B(1), a ceramide synthetase inhibitor, completely blocked FFA-induced DNA laddering in cultured ZDF islets. [(3)H]Palmitate incorporation in [(3)H]ceramide in ZDF islets was twice that of controls, but [(3)H]palmitate oxidation was 77% less. Triacsin C, an inhibitor of fatty acyl-CoA synthetase, and troglitazone, an enhancer of FFA oxidation in ZDF islets, both blocked DNA laddering. These agents also reduced inducible nitric oxide (NO) synthase mRNA and NO production, which are involved in FFA-induced apoptosis. In ZDF obesity, β cell apoptosis is induced by increased FFA via de novo ceramide formation and increased NO production.